PEREMPUAN PEKERJA (STATUS DAN PERAN PEKERJA PEREMPUAN PENJAGA WARUNG MAKAN KURNIA) - Sabariman, Hoiril (Jurnal Analisa Sosiologi, 2019)
Women who are involved in the productive sector are increasing. This article tries to explain the factors that cause women to work in the public sector, what is the status of women workers in the family and community. Direct observations and interviews were conducted with women workers in the village Ponteh. Data shows, women workers in the public sector are caused, firstly; public perception, if not working in the productive sector is not called a worker. So that forced women to work in the productive sector. Second, economic motives because they want to help the family economy. Third; as the need for self-actualization and to eliminate loneliness at home. Fourth; prestige. While the status of working women is involved in the family economy, there are even women who are the backbone of the family. Changing people's views of women. Women are no longer considered as a complement in the household, but rather are a determinant of household survival. The scientific contribution of this article is to increase understanding that women workers can become equal partners with men, both in the family and in the community. Keywords: Women workers, productive sector, status. AbstrakPerempuan yang terlibat pada sektor produktif semakin meningkat. Artikel ini mencoba menjelaskan faktor penyebab perempuan bekerja di sektor publik, bagaimana status bagi perempuan pekerja dalam keluarga dan lingkungan masyarakat. Pengamatan langsung dan wawancara dilakukan terhadap perempuan pekerja di desa Ponteh. Data menunjukkan, perempuan pekerja di sektor publik disebabkan, pertama; persepsi masyarakat, jika tidak bekerja di sektor produktif bukan disebut sebagai pekerja. Sehingga memakasa perempuan untuk bekerja disektor produktif. Kedua, motif ekonomi karena ingin membantu perekonomian keluarga. Ketiga; sebagai kebutuhan aktualisasi diri dan menghilangkan kesepian di rumah. Keempat; gengsi. Sedangkan status perempuan pekerja yang terlibat dalam perekonomian keluarga, bahkan ada perempuan yang menjadi tulang punggung keluarga. Mengubah pandangan masyarakat terhadap perempuan. Perempuan tidak lagi dianggap sebagai pelengkap dalam rumah tangga, akan tetapi menjadi penentu kelangsungan hidup rumah tangga. Kontribusi keilmuan artikel ini adalah, menambah pemahaman bahwa perempuan pekerja dapat menjadi mitra yang sejajar dengan laki-laki, baik dalam keluarga dan lingkungan masyarakat. Kata kunci: Perempuan pekerja, sektor produktif, status